Effect of Reversing-Current Operation on the Structure and Electrochemical Performance Evolution of Ni-YSZ Fuel Electrodes. Issue 10 (31st July 2018) - Liu, Qinyuan; Wang, Hongqian; Kennouche, David; Riscoe, Casey; Butts, Danielle; Barnett, Scott A.
Abstract : In reversible operation of solid oxide cells for energy storage applications, the current direction switches periodically as the cell alternates between fuel cell and electrolysis modes. Here we report the effect of this alternating current operation on Ni-YSZ fuel electrodes in 1000 h life tests at different current densities. Ni-YSZ/YSZ/Ni-YSZ symmetric cells were used because they allow relatively straightforward interpretation of electrochemical results. At constant cell current density values ⩽ 0.4 A/cm 2, the cell voltage and total resistance values were reasonably stable, with a slight reduction in RP . At current densities ≥ 0.6 A/cm 2, voltage and total cell resistances were still approximately constant, but there was a steady increase in the RΩ that was almost offset by a decrease in RP . The higher current densities resulted in damage to the electrode/electrolyte interface structure including delamination, explaining the RΩ increase. Increasing the current density also produced more Ni and YSZ nanoparticles in the electrode, yielding the decrease of RP .